Exercise-induced modulation of myokine irisin in bone and cartilage tissue—Positive effects on osteoarthritis: A narrative review - Ning, Ke; Wang, Zhuo; Zhang, Xin-an (Frontiers in Aging Neuroscience, 2022)
Osteoarthritis is a chronic degenerative musculoskeletal disease characterized by pathological changes in joint structures along with the incidence of which increases with age. Exercise is recommended for all clinical treatment guidelines of osteoarthritis, but the exact molecular mechanisms are still unknown. Irisin is a newly discovered myokine released mainly by skeletal muscle in recent years—a biologically active protein capable of being released into the bloodstream as an endocrine factor, the synthesis and secretion of which is specifically induced by exercise-induced muscle contraction. Although the discovery of irisin is relatively recent, its role in affecting bone density and cartilage homeostasis has been reported. Here, we review the production and structural characteristics of irisin and discuss the effects of the different types of exercise involved in the current study on irisin and the role of irisin in anti-aging. In addition, the role of irisin in the regulation of bone mineral density, bone metabolism, and its role in chondrocyte homeostasis and metabolism is reviewed. A series of studies on irisin have provided new insights into the mechanisms of exercise training in improving bone density, resisting cartilage degeneration, and maintaining the overall environmental homeostasis of the joint. These studies further contribute to the understanding of the role of exercise in the fight against osteoarthritis and will provide an important reference and aid in the development of the field of osteoarthritis prevention and treatment.